Bridging the global digital divide - James, Jeffrey; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2003)
Employing a rigorous analytical framework, the author bases his analysis on the concept of international technological dualism. He argues that one possible solution to the problem is the availability of affordable technologies, such as low-cost computers, which are specifically designed for the income levels and socio-economic conditions of developing countries. He also emphasises that the most important aim of any policy measure should be to provide universal access to information technologies, rather than individual ownership. Depending on whether or not this divide can be bridged will, to a large degree, determine whether developing countries are able to attain higher levels of productivity, prosperity and global integration.
pt. 1. Explaining the global digital divide -- pt. 2. Bridging the global digital divide.
Includes bibliographical references and index.
Keywords: Digital divide -- Developing countries; Electronic books